Diplomasi Publik Pemerintah Kabupaten Samosir melalui Festival Samosir Music International 2018 - Daniel Walman Hutasoit; Windy Dermawan (Universitas Padjadjaran, 2019)
The purpose of this article is to describe how public diplomacy is carried out by the Samosir Regency Government through the festival Samosir Music International 2018. The concepts used in this article are the three dimensions of public diplomacy by Joseph Nye; Soft Power; and Sub-Actors national in Public Diplomacy. This research used qualitative research methods. This research found that festival Samosir Music International 2018 had utilizied the role of mass media as a daily communication. In order to create more efficient and targeted communication, the Samosir Regency Government had conducted a series of events and the Indonesian music community as a strategic communication medium. In the end, the relationships between related actors, such as national and international music communities, artists, and media partners were the supporters of the creation of sustainable long-term Relationships. Artikel ini bertujuan mendeskripsikan diplomasi publik yang dilakukan Pemerintah Kabupetan Samosir melalui festival Samosir Music International 2018. Konsep yang digunakan ialah: tiga dimensi publik oleh Joseph Nye (Komunikasi Sehari-hari, Komunikasi Strategis, dan Pembangunan Hubungan Jangka Panjang), Soft Power, dan Aktor Sub-nasional dalam Diplomasi Publik. Artikel ini menggunakan metode kualitatif deskriptif. Artikel ini menemukan bahwa festival Samosir Music International tahun 2018 memanfaatkan peran media massa sebagai media komunikasi sehari-hari. Demi menciptakan komunikasi yang lebih efisien dan terarah, Pemerintah Kabupaten Samosir melakukan rangkaian acara dan para komunitas musik Indonesia sebagai media komunikasi strategis. Pada akhirnya, hubungan yang terjalin atara aktor-aktor terkait, seperti para komunitas musik nasional maupun internasional, artis, dan media partner yang menjadi pendukung terciptanya pembangunan hubungan jangka panjang yang berkesinambungan